HOW DO STUDENTS THINKING PROCESS IN SOLVING THE VISUALLY REPRESENTED QUESTIONS? - Beatric Videlia Remme'; Lusiana Delastri (Jurnal Pengajaran MIPA, 2022)
Problems that are represented visually can develop students' relational and logical understanding. Relational and logical understanding in geometry learning can reinforce certain relationships and develop cognitive functions, such as knowledge construction. In the process of constructing knowledge and constructing problem solving requires students' thinking processes. This study aims to describe students' thinking processes in solving problems that are represented visually. The thought process is based on reflective abstraction. The type of research that is appropriate to achieve these objectives is qualitative. The research subjects are 4 students who have studied the material of flat shapes. The results showed that the concepts represented visually could inspire various ideas in solving problems. In solving problems, the thinking process based on reflective abstraction depends on the history of the solver's knowledge. The mental mechanisms that occur when solving problems with visual representations are interiorization, coordination and encapsulation. Concepts presented using visual representations can increase in-depth understanding, but can also be a source of misconceptions for students. Error answers obtained are the result of misconceptions about concepts/information that have been interiorized into concepts presented using visual representations.